Fluvastatin Promotes Treg Cell Production in Allogeneic Immune Reaction and Suppresses Inflammatory Response - Xianxian Chen; Dong Huang; Li Zhao; Donghai Tang; Yu Tian; Chunxiao Ren; Fen Yan; Kailin Xu; Kai Zhao (Immunity, Inflammation and Disease, 2025)
ABSTRACT Introduction Statins, a class of HMG‐CoA reductase inhibitors, exhibit prophylactic benefits against immune rejection induced by allogeneic hematopoietic stem cell transplantation (allo‐HSCT). Despite the protective function is confirmed, the precise mechanism to induce immune tolerance of statin in the initial stages of transplantation remains incompletely understood. Given that Treg cells play a critical role in preventing graft versus host response and Foxp3 as a transcription factor of Treg can be induced by statins, we hypothesize that the immunosuppressive effects of statins are partially mediated through regulation of Treg cells expansion. Methods T cells were stimulated in vitro under anti‐CD3/anti‐CD28/IL‐2/TGF‐β condition or allo‐reactive system with or without the addition of statins. The induction of Tregs were detected using flow cytometry. Allo‐HSCT models were established by transferring donor cells alone or combined with recipient treated by fluvastatin. The proportions of Treg and phenotypes of effector T cells were identified. Cytokine secretion and antigen‐presenting cell (APC) function were tested in irradiated mice. Results Statins induced higher Treg production in classical and allogeneic cell co‐culture conditions in vitro. In the early stage of models treated with fluvastatin only in donors or combined treatment of donors and recipients, a similar phenomenon was observed with elevated levels of Foxp3+ Treg along with increased expression of CCR7, CD62L, and S1P1 on allo‐reactive T cells. Fluvastatin treatment suppressed the secretion of pro‐inflammatory cytokines IFN‐γ and TNF‐α by CD4+ and CD8+ T cells in irradiated mice. Furthermore, fluvastatin also contributed to restraining the numbers and activation of APCs, including dentritic cells (DCs) and macrophages in vitro and in vivo. Conclusion Our finding demonstrated that statin exposure modulates immune responses during the initial phase of allo‐HSCT by promoting Treg expansion and suppressing inflammatory reactions, which supply a promising strategy for aGVHD prevention.